2021
DOI: 10.1055/a-1515-9630
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the ‘Atrial Fibrillation Better Care’ Pathway in Patients with Atrial Fibrillation: Impact on Clinical Outcomes—A Systematic Review and Meta-Analysis of 285,000 Patients

Abstract: Aims: The ‘Atrial Fibrillation Better Care’ (ABC) pathway has been recently proposed as a holistic approach for the comprehensive management of patients with Atrial Fibrillation (AF). We performed a systematic review of current evidence for the use of the ABC pathway on clinical outcomes. Methods and Results: We performed a systematic review and meta-analysis according to PRISMA Guidelines. Pubmed and EMBASE were searched for studies reporting the prevalence of ABC pathway adherent management in AF patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
218
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 307 publications
(227 citation statements)
references
References 36 publications
8
218
0
1
Order By: Relevance
“…Previous studies have shown that therapies compliant with the holistic care (ABC compliance group) were associated with a significantly lower all-cause death and the composite outcome consisting of cardiovascular motality, myocardial infarction, ischemic stroke, total hospitalizations and major bleeding, compared with non-ABC compliant group (7)(8)(9)(10)(11)(12). Also, a system review and a meta-analysis have revealed an obvious risk reduction in ABC group despite the variation including population selection, definition of ABC and clinical outcomes among these studies (20,21). Our findings are consistent with the foregoing studies presenting lower hazard of all-cause death and the composite outcome in patients compliant with ABC care in comparsion to those without ABC pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that therapies compliant with the holistic care (ABC compliance group) were associated with a significantly lower all-cause death and the composite outcome consisting of cardiovascular motality, myocardial infarction, ischemic stroke, total hospitalizations and major bleeding, compared with non-ABC compliant group (7)(8)(9)(10)(11)(12). Also, a system review and a meta-analysis have revealed an obvious risk reduction in ABC group despite the variation including population selection, definition of ABC and clinical outcomes among these studies (20,21). Our findings are consistent with the foregoing studies presenting lower hazard of all-cause death and the composite outcome in patients compliant with ABC care in comparsion to those without ABC pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review, AF patients treated according to the ABC pathway showed a lower risk of all-cause death (odds ratio [OR]: 0.42, 95% confidence interval [CI]: 0.31-0.56), cardiovascular death (OR: 0.37, 95% CI: 0.23-0.58), stroke (OR: 0.55, 95% CI: 0.37-0.82), and major bleeding (OR: 0.69, 95% CI: 0.51-0.94). 3 Improved clinical outcomes with ABC pathway compliance are evident, even in clinically complex patients such as those with multimorbidity, polypharmacy, and hospitalizations. 4 The mAFA-II trial was a prospective cluster-randomized trial of patients randomized to receive usual care, or integrated care based on the ABC pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The use of rate and rhythm control to reduce the burden of symptoms is one of the pillars of the ABC pathway [1]. Such a structured approach to holistic AF care, including proactive risk evaluation and management, has been shown to be associated with improved clinical outcomes, especially with a reduction in hospitalizations and clinical events [19,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%